The diagnosis and management of CMV colitis in IBD patients shows high practice variation: a national survey among gastroenterologists. (2nd November 2022) - Goetgebuer, R. L.; van der Woude, C. J.; Bakker, L.; van der Eijk, A. A.; de Ridder, L.; de Vries, A. C.
Abstract: Background: Clinical guidelines on cytomegalovirus (CMV) colitis in inflammatory bowel disease (IBD) are hampered by the low quality of evidence. In this study, we aim to explore the attitude and management of CMV colitis in IBD among gastroenterologists. Methods: A web-based survey was distributed to adult and pediatric gastroenterologists and trainees in academic and general hospitals in the Netherlands. The survey comprised data collection on respondents' demographics, attitudes towards the importance of CMV infection in IBD on a visual analogue scale (from 0 to 100), and diagnostic and therapeutic strategies. Results: A total of 73/131 invited respondents from 32 hospitals completed the survey (response rate of 56%). The importance of CMV infection was scored at a median 74/100. Respondents indicated CMV testing as appropriate in the clinical setting of steroid-refractory colitis (69% of respondents), hospitalized patients with active colitis (64%), immunomodulator or biological refractory colitis (55%) and active colitis irrespective of medication use (14%). CMV diagnostics include histology of colonic biopsies (88% of respondents), tissue CMV PCR (43%), serum CMV PCR (60%), CMV serology (25%) and fecal CMV PCR (4%). 82% of respondents start antiviral therapy after a positive CMV test on colonic biopsies (histology or PCR). Conclusions: Most Dutch gastroenterologists acknowledge the importance of CMV colitis in IBD. Strategies vary greatly with regard to the indication for testing and diagnostic method, as well as indication for the start of antiviral therapy. These findings underline the need for pragmatic clinical studies on different management strategies, in order to reduce practice variation and improve the quality of care. Summary of the established knowledge on this subject: The clinical significance of CMV-associated colitis in IBD remains a matter of debate Recommendations regarding CMV colitis in current international guidelines are based on low to moderate evidence levels and different diagnostic strategies are proposed What are the significant and/or new findings of this study?: We show that there is a high practice variation of diagnosis and management of CMV colitis in IBD amongst adult and pediatric gastroenterologists This study underlined the need for pragmatic studies and guidelines on different management strategies including cut-off values to start therapy